Investigation of Solar-Powered Geothermal Heat Pump System for decarbonizing space heating at Thunder Bay Regional Health Sciences Centre, Northwestern Ontario - Nagi, Anjali (My University, 2026)
This thesis investigates the technical feasibility, economic viability, and environmental impact of implementing a Solar-Powered Geothermal Heat Pump (SP-GHP) system to decarbonize space heating at the Thunder Bay Regional Health Sciences Centre (TBRHSC) in Northwestern Ontario. Decarbonizing the heating sector in extreme cold climates is a critical challenge, as conventional systems in such regions are typically carbon-intensive and fossil-fuel reliant. The research employs an integrated methodology combining experimental laboratory testing, regional geological characterization, building energy modeling, and solar photovoltaic (PV) optimization. Experimental results from a lab-scale geothermal heat pump simulator at Lakehead University validated the system's thermal responsiveness, demonstrating that supply air temperatures and Coefficient of Performance (COP) increase linearly with entering water temperatures. Utilizing regional soil data from the nearby Musselwhite mine, the study identified that ground temperatures are most favorable at a shallow depth of approximately 5 meters, which avoids the high costs of deep drilling. A detailed heat load analysis for the 650,000 ft² facility estimated a peak heating load of 640 kW and an annual demand of 1.43 GWh. To meet this demand, a horizontal slinky-loop ground heat exchanger was designed, requiring approximately 20 km of pipe. Furthermore, location-specific solar simulations determined an annual average optimum tilt angle of 39°, while a load-responsive winter tilt of 67° was proposed to synchronize solar electricity generation with peak winter heating requirements. Techno-economic and environmental assessments conducted via RETScreen Expert software revealed that the proposed system would achieve a 96.4% reduction in annual heating-related greenhouse gas emissions. While the project requires a substantial initial investment of approximately $3 million, sensitivity analysis suggests it becomes financially viable with a payback period of 12 to 15 years when supported by clean energy incentives and carbon pricing. This study concludes that integrated SP-GHP systems represent a technically sound and environmentally advantageous solution for advancing low-carbon transitions in large-scale institutional buildings like hospital, within extreme cold climatic regions.
Thesis embargoed until April 22, 2027.